2022
DOI: 10.3389/fchem.2022.991481
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic-deposited MXene titanium coatings in regulating bacteria and cell response for peri-implantitis

Abstract: Background: Two-dimensional(2D)MXenes have continued to receive increasing interest from researchers due to their graphene-like properties, in addition to their versatile properties for applications in electronic devices, power generation, sensors, drug delivery, and biomedicine. However, their construction and biological properties as titanium coatings to prevent peri-implantitis are still unclear.Materials and methods: In this work, few-layer Ti3C2Tx MXene coatings with different thicknesses at varied deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…This was in accordance with the previous findings, in which Ti 3 C 2 T x NSs exhibited antioxidant activity. 53,54 These results suggested that the ROS might not be a major factor for the antibacterial activity is this study.…”
Section: Resultsmentioning
confidence: 51%
“…This was in accordance with the previous findings, in which Ti 3 C 2 T x NSs exhibited antioxidant activity. 53,54 These results suggested that the ROS might not be a major factor for the antibacterial activity is this study.…”
Section: Resultsmentioning
confidence: 51%
“…Moreover, there are numerous studies that confirm the opposite – their anti‐inflammatory effect [15,18,33,34,99] . Also, they demonstrate some positive effects, for example, antiapoptotic, [19,20] osteoinductive activity, [36,100] or antioxidant activity [19,51,99,101,102] . Importantly, toxicity studies of MXenes in rodents summarized in Table 4 did not show any signs of tissue damages or functional differences.…”
Section: Stability Biodegradability Toxicity and Biocompatibility Of ...mentioning
confidence: 95%
“…[15,18,33,34,99] Also, they demonstrate some positive effects, for example, antiapoptotic, [19,20] osteoinductive activity, [36,100] or antioxidant activity. [19,51,99,101,102] Importantly, toxicity studies of MXenes in rodents summarized in Table 4 did not show any signs of In general, all of the above makes them suitable for biological application. However, in fact, the use of MXenes in biomedicine is currently a fairly new and poorly studied direction.…”
Section: R E V I E W T H E C H E M I C a L R E C O R Dmentioning
confidence: 97%
“…Pure MXene can be used in antimicrobial applications in the form of coatings. Huang et al ( Huang et al, 2022 ) prepared Ti 3 C 2 T x coating on the surface of plain titanium by anodic electrophoretic deposition. The experimental data shows that the coating has great hydrophilicity and bonding strength, which can inhibit the adhesion of S. aureus and MRSA and hinder biomembrane formation, effectively preventing the peri-implantitis.…”
Section: Application Of Mxene In the Antimicrobial Fieldmentioning
confidence: 99%